Evaluation of the anti-inflammatory, antinociceptive, and antipyretic potential of ethanolic extract of Aristida depressa Retz through in vitro, in vivo, and in silico models - Sherif, Asmaa E.; Alam, Rabia; Asif, Muhammad; Khan, Kashif-ur-Rehman; Ur Rehman, Muhammad Sajid (Frontiers in Pharmacology, 2024)
Uncontrolled inflammation is a crucial factor in the development of many diseases. Anti-inflammatory molecules based on natural sources are being actively studied, among which Aristida depressa Retz (Ar.dp) has been traditionally used as a paste to heal inflammation. The present study aimed to evaluate the anti-inflammatory, analgesic, and antipyretic potential of an ethanolic extract of A. depressa through a battery of in vivo and in vitro models. The ethanolic extract of A. depressa was prepared by maceration and chemically characterized using high-performance liquid chromatography, which revealed the presence of quercetin, vanillic acid, chlorogenic acid, p-coumaric acid, m-coumaric acid, ferulic acid, cinnamic acid, and sinapic acid; its antioxidant capacity was then screened with the DPPH in vitro assay, which indicated moderate scavenging capacity. A protein denaturation assay was next performed to evaluate the in vitro anti-inflammatory potential of Ar.dp, which showed significant inhibition (44.44%) compared to the standard drug (diclofenac sodium), with 89.19% inhibition at a concentration of 1 mg/mL. The in vivo safety profile of Ar.dp was evaluated in accordance with the OECD-425 acute toxicity guidelines and found to be safe up to 5 g/kg. The in vivo anti-inflammatory potentials of Ar.dp were evaluated at three different doses (125, 250, and 500 mg/kg) in acute (carrageenan-induced edema: 84.60%, histamine-induced paw edema: 84%), sub-chronic (cotton-pellet-induced granuloma: 57.54%), and chronic (complete-Freund’s-adjuvant-induced arthritis: 82.2%) models. Our results showed that Ar.dp had significant (p < 0.05) anti-inflammatory effects over diclofenac sodium in the acute and chronic models. Histopathology studies indicated reduced infiltration of paw tissues with inflammatory cells in Ar.dp-treated animals. Similarly, Ar.dp showed significant (p < 0.05) analgesic (yeast-induced-pyrexia model: 23.53%) and antipyretic (acetic-acid-induced writhing model: 51%) effects in a time-dependent manner. In silico studies on the interactions of COX-1 and COX-2 with the eight ligands mentioned earlier confirmed the inhibition of enzymes responsible for inflammation and fever. Based on the findings of the present study, it is concluded that Ar.dp has anti-inflammatory, analgesic, and antipyretic properties that are likely linked to its pharmacologically active phenolic bioactive molecules.